Optimization of received power and SNR for an indoor attocells network in visible light communication - Mohammed Gismalla, Mohammed Salih; Abdullah, Mohammad Faiz Liew (2019)
White LEDs Visible Light Communication (VLC) is applied in communication and illumination simultaneously. It provides unrestrained frequency spectrum and a large bandwidth that produces a higher transmission rate and speed in short-range communication. Also, VLC was considered as a promising alternative technology to the radio frequency in the next generation of communication systems. In this paper, the optical attocells configuration and LEDs distribution are proposed for optimizing the received power and Signal-to-Noise Ratio (SNR) in the Line of Sight (LOS) propagation link. Besides that, the trade-off between minimum SNR and received power are investigated. The simulation results showed that the proposed model can save 6.25% of the total transmitted power, and the optical received power versus semi-angle and field of view have with about increased 16.5% and 27.54% respectively. Moreover, the SNR also has 7.4% improvement. Hence, the proposed configuration model has improved the performance of VLC systems and has widen the window for future improvement.